General Relativity, Space-time Fabric and Its Applications in Parametric Interior Design (Journal of the College of Basic Education, 2025)
Scientific theories have long played a fundamental role in shaping the principles of interior design, given their direct impact on the creative process of generating interior design elements. This study aims to highlight the concept of relativity theory and the fabric of space-time within the framework of parametric design for interior spaces. The primary objective is to analyze this concept and explore its associated ideas to identify the elements and components that encapsulate the essence of parametric design and its applications in traditionally influenced interior environments.The research is structured around the following key question: How can the application of general relativity principles, particularly the concept of space-time fabric, contribute to the advancement of parametric interior design, leading to innovative and dynamic spatial configurations that effectively interact with contemporary environments? Accordingly, the study seeks to investigate the creative potential embedded in the integration of advanced theoretical physics concepts—specifically, the distortions of space-time derived from Einstein’s general theory of relativity—into parametric interior design. It further aims to assess the extent to which these concepts can stimulate innovation in the formation of unconventional design structures, fostering the development of dynamic design solutions that engage with the spatial contexts of modern interiors while reinforcing the synergy between aesthetic and functional dimensions.To achieve these objectives, the study examines case studies of interior design projects undertaken by specialized parametric design firms. The findings reveal that the concept of space-time fabric, inspired by Einstein’s general theory of relativity, has significantly transformed parametric interior design methodologies. The study demonstrates that the curvature and distortion of space-time serve as a conceptual foundation for generating interior spaces characterized by fluidity and seamless form transitions. Moreover, the study confirms that the integration of general relativity principles with parametric design technologies can yield remarkable design outcomes. By employing complex mathematical equations, theoretical concepts can be translated into tangible visual forms, thereby enhancing both the aesthetic and functional qualities of interior spaces.